High eccentricities and high masses characterize gravitational-wave captures in galactic nuclei as seen by Earth-based detectors. Issue 2 (6th July 2021) - Gondán, László; Kocsis, Bence
ABSTRACT: The emission of gravitational waves (GWs) during single–single close encounters in galactic nuclei (GNs) leads to the formation and rapid merger of highly eccentric stellar-mass black hole (BH) binaries. The distinct distribution of physical parameters makes it possible to statistically distinguish this source population from others. Previous studies determined the expected binary parameter distribution for this source population in single GNs. Here, we take into account the effects of dynamical friction, post-Newtonian corrections, and observational bias to determine the detected sources' parameter distributions from all GNs in the Universe. We find that the total binary mass distribution of detected mergers is strongly tilted towards higher masses. The distribution of initial peak GW frequency is remarkably high between 1 and 70 Hz, \! 50 per cent of GW capture sources form above 10 Hz with e ≳ 0.95. The eccentricity when first entering the LIGO/Virgo/KAGRA band satisfies e_10 Hz0.1 for over 92 per cent of sources and e_10 Hz0.8 for more than half of the sources. At the point when the pericentre reaches 10 GM / c 2 the eccentricity satisfies e 10 M > 0.1 for over \! 70 per cent of the sources, making single–single GW capture events in GNs the most eccentric source population among the currently known stellar-mass binary BH merger channels in our Universe. We identify correlations between total mass, mass ratio, source detection distance, and eccentricities e_10 Hz and e 10 M . The recently measured source parameters of GW190521 lie close to the peak of the theoretical distributions and the estimated escape speed of the host environment is \! 7.5× 10^3\!-\!1.2× 10^4 km s^-1, making this source a candidate for this astrophysical merger channel.